Peran Program CSR PHE-WMO Terhadap Kesejarteraan Pendidik Dan Masyarakat Bangkalan - Rusdi Hanzyah (Pedir Research Institute, 2022)
This study aims to find out about how a CSR program is implemented and what benefits are obtained by the company, as well as how the feedback from the surrounding community is long-term for the company. This research uses approaches by using descriptive research methods. This study aims to find out how the CSR program is implemented and what long-term impact the company has on its implementation. Research conducted on the Community Empowerment Program (PPM) and Corporate Social Responsibility (CSR) of PT Pertamina Hulu Energi West Madura Offshore (PHE WMO) has helped the government improve the standard of living of the northern coastal community of Bangkalan. The plan has been almost entirely implemented. However, in its implementation there are still weaknesses so that the results of the implementation of the program have not been maximized. From these weaknesses, recommendations can be given, namely a clear measurement and reporting is needed so that it can be used as an evaluation for the implementation of the next program.